2022
DOI: 10.33899/ijvs.2022.132960.2153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sodium butyrate on stimulating of some host defense peptides and body performance in broiler vaccinated with different avian influenza (H9N2) vaccines

Abstract: Our study is designated to determine the impact of SB in the induction HDPs, including AvBD-10 and CATH-B1, accompanied by two different inactivated H9N2 vaccines and their effect on body performance. One hundred fifty, day-old chicks were separated into five groups (30 chicks for each, three replicates): groups A and C were vaccinated with classical avian influenza H9N2 and developed H9N2P inactivated vaccines, respectively, but groups B and D were treated with sodium butyrate (SB) by a dosage of 1gm/liter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…AIV is one of the viruses with a high potential for devastation in commercial chicken production, which results in massive economic losses, especially in breeder and layer flocks (3). Depending on the strains, hosts, and stages of infection, cytokines can have varying beneficial effects on the pathogenesis of the influenza virus (HPAI) (4,5). Studies on influenza-infected mice showed an increased inflammatory response and dysregulated cytokines, which led to a high mortality rate (6).…”
Section: Introductionmentioning
confidence: 99%
“…AIV is one of the viruses with a high potential for devastation in commercial chicken production, which results in massive economic losses, especially in breeder and layer flocks (3). Depending on the strains, hosts, and stages of infection, cytokines can have varying beneficial effects on the pathogenesis of the influenza virus (HPAI) (4,5). Studies on influenza-infected mice showed an increased inflammatory response and dysregulated cytokines, which led to a high mortality rate (6).…”
Section: Introductionmentioning
confidence: 99%